Australia 1888. - Australia 1788-1988: A Bicentennial History ([S.l. : s.n.], 1979)
Journal "devoted to research and discussion on new approaches in Australian history"--Ed. (No. 1, p. 5); Bicentennial History Project; historians.
APAIS, Australian public affairs information service
Keywords: Research - Methodology and techniques; History - Theory and criticism - Writing; Politics and Government - National symbols and events - Bicentennial, 1988.; Settlement and contacts - Colonisation - 1851-; Australia -- History -- 1788-1900 -- Periodicals; Australia